2023
DOI: 10.1186/s12978-023-01671-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cumulative live birth rate outcomes of three ovarian stimulation protocols in patients after laparoscopic cystectomy of ovarial endometrioma: a retrospective cohort study

Jiaheng Li,
Yijiang Li,
Mengnuo Li
et al.

Abstract: Background Previous studies have reported that after laparoscopic cystectomy of ovarial endometrioma, the ovarian response to gonadotropin (Gn) significantly decreased. However, for patients with diminished ovarian reserve (DOR) after ovarian surgery, how to choose the most appropriate controlled ovarian hyperstimulation protocol has not been concluded. Compared with the traditional agonist regimen, the gonadotropin (Gn)-releasing hormone (GnRH) antagonist, microstimulation, and progestin-prime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In 2019, a domestic meta-analysis included 2,270 cycles in the PPOS group and 2,463 cycles in the microstimulation group. The findings showed that compared to the microstimulation protocol, the PPOS protocol produced a higher rate of high-quality embryos and a lower rate of cycle cancellation for patients with DOR [ 11 ]. We tried PPOS treatment on a single patient, and the pregnancy was achieved in a patient with DOR.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, a domestic meta-analysis included 2,270 cycles in the PPOS group and 2,463 cycles in the microstimulation group. The findings showed that compared to the microstimulation protocol, the PPOS protocol produced a higher rate of high-quality embryos and a lower rate of cycle cancellation for patients with DOR [ 11 ]. We tried PPOS treatment on a single patient, and the pregnancy was achieved in a patient with DOR.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al analyzed PPOS protocols in a retrospective study of 89 endometriosis patients and found that those aged under 40 with DOR after laparoscopic cystectomy of endometrioma obtained similar ovulation induction outcomes and cumulative live birth rates whether they were treated with a GnRH antagonist or a PPOS protocol [27].…”
Section: Generalmentioning
confidence: 99%